2015
DOI: 10.1186/s12871-016-0184-3
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal girth and vertebral column length can adjust spinal anesthesia for lower limb surgery, a prospective, observational study

Abstract: BackgroundStudies have shown that abdominal girth and vertebral column length have high predictive value for spinal spread after administering a dose of plain bupivacaine. we designed a study to identify the specific correlations between abdominal girth, vertebral column length and a 0.5 % dosage of plain bupivacaine, which should provide a minimum upper block level (T12) and a suitable upper block level (T10) for lower limb surgeries.MethodsA suitable dose of 0.5 % plain bupivacaine was administered intrathec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
(29 reference statements)
2
17
0
Order By: Relevance
“…A high correlation between both abdominal girth and vertebral column length and lumbosacral cerebrospinal fluid volume was the primary finding of this study, which further explains the results of our previous studies . In our studies, we have demonstrated that abdominal girth and dorso‐sacral distance have a high predictive value for the spinal spread after a given dose of plain bupivacaine and can largely predict a suitable dose of plain bupivacaine for lower limb surgery.…”
Section: Discussionsupporting
confidence: 85%
“…A high correlation between both abdominal girth and vertebral column length and lumbosacral cerebrospinal fluid volume was the primary finding of this study, which further explains the results of our previous studies . In our studies, we have demonstrated that abdominal girth and dorso‐sacral distance have a high predictive value for the spinal spread after a given dose of plain bupivacaine and can largely predict a suitable dose of plain bupivacaine for lower limb surgery.…”
Section: Discussionsupporting
confidence: 85%
“…Greene 4 has described 25 factors that affect the spread of spinal anaesthesia but in clinical practice it is hard to isolate one factor and quantify its effect on the spread of spinal anaesthesia from the others. There is a great interest on defining the determinants of spinal anaesthesia spread in recent studies (5)(6)(7)(8)(9). Measures that are practically obtainable and have a predictive value on spinal anaesthesia spread will help the clinicians to predict the spread of spinal anaesthesia for individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, body height and weight are still more easily accessible than measurements of vertebral column length and abdominal girth. Recent studies and our results indicated that block level is negatively correlated with body height whereas it is positively correlated with body weight [6][7][8].…”
Section: Discussionmentioning
confidence: 73%
“…In addition, vertebral column length and abdominal girth have recently been reported as newly in uencing factors which should replace body height and weight for intrathecal drug spread [6][7][8]. Even so, body height and weight are still more easily accessible than measurements of vertebral column length and abdominal girth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation